Carbapenemase-producing Enterobacteriaceae in Europe: assessment by national experts from 38 countries, May 2015 - B Albiger; C Glasner; MJ Struelens; H Grundmann; DL Monnet; The European Survey of Carbapenemase-Producing Enterobacteriaceae (EuSCAPE) working group; Ana Kaftandzieva; Shaban Memeti (My University, 2015)
In 2012, the European Centre for Disease Prevention and Control (ECDC) launched the ‘European survey of carbapenemase-producing Enterobacteriaceae (EuSCAPE)’ project to gain insights into the occur rence and epidemiology of carbapenemase-producing Enterobacteriaceae (CPE), to increase the awareness of the spread of CPE, and to build and enhance the labo ratory capacity for diagnosis and surveillance of CPE in Europe. Data collected through a post-EuSCAPE feed back questionnaire in May 2015 documented improve ment compared with 2013 in capacity and ability to detect CPE and identify the different carbapenemases genes in the 38 participating countries, thus contrib uting to their awareness of and knowledge about the spread of CPE. Over the last two years, the epidemio logical situation of CPE worsened, in particular with the rapid spread of carbapenem-hydrolysing oxacil linase-48 (OXA-48)- and New Delhi metallo-beta lactamase (NDM)-producing Enterobacteriaceae. In 2015, 13/38 countries reported inter-regional spread of or an endemic situation for CPE, compared with 6/38 in 2013. Only three countries replied that they had not identified one single case of CPE. The ongo ing spread of CPE represents an increasing threat to patient safety in European hospitals, and a majority of countries reacted by establishing national CPE surveil lances systems and issuing guidance on control meas ures for health professionals. However, 14 countries still lacked specific national guidelines for prevention and control of CPE in mid-2015
Keywords: Antimicrobial resistance; Europe; Gram negative; Infection prevention and control; Carbapenemase-producing Enterobacteriaceae (CPE); Surveillance